A modified Adomian decomposition method for singular initial value Emden-Fowler type equations - Biazar, Jafar; Hosseini, Kamyar (International Journal of Applied Mathematical Research, 2016)
Traditional Adomian decomposition method (ADM) usually fails to solve singular initial value problems of Emden-Fowler type. To overcome this shortcoming, a new and effective modification of ADM that only requires calculation of the first Adomian polynomial is formally proposed in the present paper. Three singular initial value problems of Emden-Fowler type with alpha=1, 2, and >2, have been selected to demonstrate the efficiency of the method. Â Â Â